Conspicuous consumption and satisfaction - Rainer Winkelmann (University of Zurich, Department of Economics, 2011)
Traditional tools of welfare economics identify the envy-related welfare loss from conspicuous consumption only under very strong assumptions. Measured income and life satisfaction offers an alternative for estimating such consumption externalities. The approach is developed in the context of luxury car consumption (Ferraris and Porsches) in Switzerland. Results from household panel data and fixed effects panel regressions suggest that the prevalence of luxury cars in the municipality of residence has a negative impact on own income satisfaction.
Keywords: D12; D62; I31; 330; Ferrari; Porsche; status; consumption externality; Swiss Household Panel; Luxusgut; Kraftfahrzeug; Konsuminterdependenz; Sozialer Status; Zufriedenheit; Schweiz